(untitled) (Bangladesh Journal of Otorhinolaryngology, 2020)
Background: Chronic Otitis Media (COM) is a common disease in our country. COM with or without cholesteatoma may lead to ossicular discontinuity. However, the discontinuity of the ossicular chain is usually confirmed during operation. The purpose of the study was to find out the correlation between preoperative hearing loss and the status of ossicular chain at surgery. Methods: This cross-sectional study was conducted in the department of otolaryngology- Head & neck surgery, Bangabandhu Sheikh Mujib Medical University from January 2013 to June 2014. At least 113 patients of COM were selected as per inclusion and exclusion criteria. Relevant data were collected in a predesigned data collection sheet and analyzed with standard statistical method. Statistically significant inferred for P value <0.05. No groups whose ability to give voluntary informed consent questionable was not included. No potential risks exist in designed this study. Results: Out of 34 patients with mild degree of hearing loss 31(39.7%) had intact ossicular chain whereas discontinuity was seen in 3(8.6%) cases, 37 patients with moderate degree of hearing loss 16(45.7%) had ossicular discontinuity. Among 23 patients with moderate to severe degree of hearing loss 14(17.9%) had intact ossicular chain whereas ossicular discontinuity was found 9(25.7%), 9 patients of severe degree of hearing loss 7(20%) had ossicular discontinuity. Cases with moderate and severe degree of hearing loss had significant ossicular discontinuity (p<0.05). Air-bone gap > 40 dB was found in 60% cases of ossicular discontinuity, followed by air bone gap 31-40 dB(17.14%), 21-30 dB(14.29%) and 11-20 dB( 8.57%) respectively. So ossicular discontinuity was in higher air-bone gap group and it was statistically significant (p<0.001). Bangladesh J Otorhinolaryngol; October 2019; 25(2): 94-101